Evaluasi Perencanaan Sistem Drainase di Kelurahan Cisaranten Endah, Kecamatan Arcamanik, Kota Bandung - Eka Wardhani; Idza Selvia; Iwan Juwana; Athaya Zahrani Irmansyah (Jurnal Serambi Engineering, 2026)
This study examines the drainage system on Jl. Aeromodeling IV, Cisaranten Endah Village, Arcamanik District, Bandung City, which experiences flooding problems due to the suboptimal capacity of the drainage channels. The purpose of this study is to identify, analyze, and provide alternative results from the evaluation of the existing drainage system and planning. The research methods include collecting primary data through observation of the existing drainage conditions and secondary data in the form of regional maps, which are then analyzed using a hydrological approach to calculate the planned discharge and channel dimensions. The results of the study show that there are several points in the drainage system that are unable to accommodate runoff discharge, namely at points P6-P1. The proposed alternative solution is to widen the drainage system at points P6-P1 to increase its capacity in accordance with the planned discharge, as well as to install floodgates and pump houses to transfer water from the flooded area to the receiving river.